Lettuce Wars - Neuburger, Bruce (Book collections on Project MUSE., 2013)
In 1971, Bruce Neuburger--young, out of work, and radicalized by the 60s counterculture in Berkeley--took a job as a farmworker on a whim. He could have hardly anticipated that he would spend the next decade laboring up and down the agricultural valleys of California, alongside the anonymous and largely immigrant workforce that feeds the nation. This account of his journey begins at a remarkable moment, after the birth of the United Farm Workers union and the ensuing uptick in worker militancy. As a participant in organizing efforts, strikes, and boycotts, Neuburger saw first-hand the struggles of farmworkers for better wages and working conditions, and the lengths the growers would go to suppress worker unity. Part memoir, part informed commentary on farm labor, the U.S. labor movement, and the political economy of agriculture, Lettuce Wars is a lively account written from the perspective of the fields. Neuburger portrays the people he encountered--immigrant workers, fellow radicals, company bosses, cops and goons--vividly and indelibly, lending a human aspect to the conflict between capital and labor as it played out in the fields of California.